Quantum Interference Effects in Quantum Dot Molecular With Majorana Bound States - Chi, Feng; Wang, Jing; He, Tian-Yu; Fu, Zhen-Guo; Zhang, Ping; Zhang, Xiao-Wen; Wang, Lihui; Lu, Zongliu (Frontiers in Physics, 2021)
Non-invasive detection of the Majorana bound state (MBSs), a kind of quasiparticle without charge and mass, is one of the core issues in current condensed matter physics. Here we study in theory the quantum interference effect in parallel-coupled double quantum dots (QDs) which are connected either by Majorana bound states (MBSs) or regular fermions. We find that the zero-energy conductance emerges a sharp peak when the dots are connected by the MBSs, whereas that in the case of the dots are coupled via regular fermions is a valley. By varying the coupling strength between the dots and the electron reservoirs, the conductance in the two structure changes in different ways. By comparing the properties of the linear conductance in the two systems, the information of the MBSs formed at the two ends of a topological superconductor nanowire then can be inferred. We also find that the MBSs in the present structure also leads to the Fano effect, and is favorable in quantum information processing.